Overexpression Levels of LbDREB6 Differentially Affect Growth, Drought, and Disease Tolerance in Poplar - Yang, Jingli; Wang, Hanzeng; Zhao, Shicheng; Liu, Xiao; Zhang, Xin; Wu, Weilin; Li, Chenghao (Frontiers in Plant Science, 2020)
The application of drought stress-regulating transcription factors (TFs) offers a credible way to improve drought tolerance in plants. However, many drought resistant TFs always showed unintended adverse effects on plant growth or other traits. Few studies have been conducted in trees to evaluate and overcome the pleiotropic effects of drought tolerance TFs. Here, we report the dose-dependent effect of the Limonium bicolor LbDREB6 gene on its overexpression in Populus ussurensis. High- and moderate-level overexpression of LbDREB6 significantly increased drought tolerance in a dose-dependent manner. However, the OE18 plants showed stunted growth under normal conditions, but they were also more sensitive to Marssonina brunnea infection than wild type (WT) and OE14 plants. While, OE14 showed normal growth, the pathogen tolerance of them was not significantly different from WT. Many stress-responsive genes were up-regulated in OE18 and OE14 compared to WT, especially for OE18 plants. Meanwhile, more pathogen tolerance related genes were down-regulated in OE18 compared to OE14 and WT plants. We achieved improved drought tolerance by adjusting the increased levels of exogenous DREB genes to avoid the occurrence of growth reduction and reduced disease tolerance.